2015
DOI: 10.1177/2047487315624747
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate and measures of effort-related cardiac autonomic dysfunction predict cardiovascular events in asymptomatic type 2 diabetes

Abstract: Chronotropic incompetence, resting tachycardia and reduced heart rate recovery are independently and additively associated with long-term mortality, myocardial infarction or stroke in type 2 diabetes without known coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
(50 reference statements)
0
26
1
Order By: Relevance
“…The autonomic nervous system, combined with the sympathetic and parasympathetic nerves, largely acts unconsciously and regulates various bodily functions such as heart rate, digestion, respiratory rate, and pupillary response. In recent times, the concept of autonomic nervous modulation has been applied to healthcare management in various fields other than medical treatment (Lucini et al, 1997; Singh et al, 2004; Sakuragi and Sugiyama, 2006; Mizuno et al, 2011; Tanaka et al, 2011) and to the risk management of diseases such as arrhythmia and cardiovascular disease (Zimmerman et al, 1988; Barutcu et al, 2014; Zafrir et al, 2016). Autonomic nervous activation in a large range of emotions was previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…The autonomic nervous system, combined with the sympathetic and parasympathetic nerves, largely acts unconsciously and regulates various bodily functions such as heart rate, digestion, respiratory rate, and pupillary response. In recent times, the concept of autonomic nervous modulation has been applied to healthcare management in various fields other than medical treatment (Lucini et al, 1997; Singh et al, 2004; Sakuragi and Sugiyama, 2006; Mizuno et al, 2011; Tanaka et al, 2011) and to the risk management of diseases such as arrhythmia and cardiovascular disease (Zimmerman et al, 1988; Barutcu et al, 2014; Zafrir et al, 2016). Autonomic nervous activation in a large range of emotions was previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that in the presence of diabetes, the relationship between obesity and mortality may not be independent. In particular, diabetes is characterized by autonomic dysfunction with sympathetic activation, which is associated with increased morbidity and mortality . Thus, the positive impact of an attenuated sympathetic activation in obese patients with HF could be blunted by the presence of the metabolic disorder.…”
mentioning
confidence: 99%
“…In this Framingham Heart Study offspring cohort these measures, in addition to smoking, age, and gender, were shown to be significant predictors for developing CVD, DM, and early mortality within 12 years. Zafrir et al (2016) also showed that resting tachycardia (HR > 100 beats/minute), chronotropic incompetence (inability of the heart to increase its rate commensurate with increased activity or demand), and reduced HR recovery after treadmill exercise were independently correlated with stroke, MI, and overall mortality in T2DM patients (hazard ratios of 1.97, 1.89, and 1.77, respectively), regardless of established coronary heart disease. In addition, the EURODIAB Prospective Cohort Study (Soedamah-Muthu et al, 2008) revealed that CAN was the most distinctive predictor for mortality in a large group of patients with T1DM, and increased mortality risk with deteriorating CAN was shown in a meta-analysis of several trials (Maser et al, 2003).…”
Section: Cardiac Autonomic Neuropathy and Risk Of Cardiovascular Evenmentioning
confidence: 95%